Bench-scale bubbling fluidized bed systems around the world - Bed agglomeration and collapse: A comprehensive review. (25th May 2021) - Nascimento, Francisco Regis Machado; González, Aldemar Martínez; Silva Lora, Electo Eduardo; Ratner, Albert; Escobar Palacio, Jose Carlos; Reinaldo, Rafaela
Abstract: Thermochemical conversion by gasification process is one of the most relevant technologies for energy recovery from solid fuel, with an energy conversion efficiency better than other alternatives like combustion and pyrolysis. Nevertheless, the most common technology used in the last decades for thermochemical conversion of solid fuel through gasification process, such as coal, agriculture residues or biomass residues are the fluidized bed or bubbling fluidized bed system. For these gasification technologies, an inert bed material is fed into reactor to improve the homogenization of the particles mixture and increase the heat transfer between solid fuel particles and the bed material. The fluidized bed reactors usually operate at isothermal bed temperatures in the range of 700–1000 °C, providing a suitable contact between solid and gas phases. In this way, chemical reactions with high conversion yield, as well as an intense circulation and mixing of the solid particles are encouraged. Moreover, a high gasification temperature favours carbon conversion efficiency, increasing the syngas production and energy performance of the gasifier. However, the risk of eutectic mixtures formation and its subsequent melting process are increased, and hence the probability of bed agglomeration and the system collapse could be increased, mainly when alkali and alkaline earth metals-rich biomasses are considered. Generally, bed agglomeration occurs when biomass-derived ash reacts with bed material, and the lower melting temperature of ash components promotes the formation of highly viscous layers, which encourages the progressive agglomerates creation, and consequently, the bed collapse and system de-fluidization. Taking into account the relevance of this topic to ensure the normal gasification process operating, this paper provides several aspects about bed agglomeration, mostly for biomass gasification systems. In this way, chemistry and mechanism of bed agglomeration, as well as, some methods for in-situ detection and prediction of the bed agglomeration phenomenon are reviewed and discussed. Highlights: Bed agglomeration depends on alkali metals content of biomass and temperature. Ash-based alkali metals favor eutectic compounds formation and bed agglomeration. High temperatures promote carbon conversion and melting eutectic mixtures. Mechanisms for fluidized bed agglomeration and de-fluidization were identified. Methods for detection and prediction of bed agglomeration process were reviewed.